The use of amino acid formulas in pediatric patients with allergy to cow’s milk proteins: Recommendations from a group of experts - Ribes-Koninckx, Carmen; Amil-Dias, Jorge; Espin, Beatriz; Molina, Manuel; Segarra, Oscar; Diaz-Martin, Juan J. (Frontiers in Pediatrics, 2023)
One of the most common food allergies in children is cow’s milk allergy (CMA). In breast-fed infants with CMA, the mother is encouraged to avoid dairy products. If this is not possible, or in formula fed infants, use of hypoallergenic replacement formulas such as extensively hydrolyzed formulas (EHF) is recommended. However, in ~5% of patients EHFs are not tolerated and/or allergy symptoms can persist. When EHFs are ineffective and in severe forms of CMA, amino acid-based formulas (AAF) should be considered. Six pediatric gastroenterologists with extensive experience in food allergy management reviewed scientific publications and international clinical practice guidelines to provide practical recommendations on AAF. The guidelines reviewed had discrepancies and ambiguities around the specific indications for using formulas as a milk substitute. The panel recommends AAFs as the first therapeutic option in anaphylaxis due to CMA, in acute and chronic severe food protein-induced enterocolitis syndrome, in CMA associated with multiple food allergy, and in cases of eosinophilic esophagitis not responding to an extended exclusion diet or not eating solids. The main benefit of AAF is its absence of residual allergenicity, making it a safe treatment option in severe CMA patients who do not tolerate or respond to an EHF.